(untitled) (Applied Biological Research, 2018)
Prevalence of vitamin B12 deficiency has increased in community in recent time. The present study was done to assess vitamin B12 status with respect to age and sex. Vitamin B12 assays were performed on 1512 individuals from a North Indian Lacto vegetarian community and further validated on a familial sample of 79 individuals. Individuals were considered to be , if vitamin B12 levels were <220 pg mL-1. Median levels of vitamin B12 was below the normal range i.e. <220 pg mL-1. Significant differences in median levels between males and females were observed (Mann-Whitney p<0.01). The results revealed no significant differences in females (χ2 value= 37.82, p<0.01). Similar results among the families possibly indicate multigenerational dietary inadequacy along with the changes in lifestyle apart from vegetarian diet.